Dragon Fruit Giving Effect Against Malondealdehıde (MDA) Levels in Muay Thaı Athletes With Hıgh Intensıty Interval Traınıng (HIIT) Method - Hakim, Abdul Latif Rahman; Ambardini, Rachmah Laksmi; Nugroho, Wildan Alfia; Burhaein, Erick (Journal of Education, Health and Sport, 2018)
Aim: The aim of this research is to know how much the level of decline in MDA levels in muay thai athletes with HIIT Tabata training method.Methods: This research using experimental method with eighteen times of treatments using pretest-posttest control group design with true experimental lbortories research. The subjects of this research are 20 muay thai athletes. The subject divided into two groups they are control group and experimental group (who consume dragon fruit). The way of collecting the data in this research is by taking the blood from sample’s ven ante cubiti. Then the blood will be taken to the laboratory to measure the level of Malondealdehıde from control group, treatment group 1 and 2 by using TBARS method. The data analysis is using three steps of testing which is normal testing, homogeneity testing and hypothesis testing. Results: The results obtained in this research are: 1) the data obtained from normality testing of significance score from every group >0,05 so that the data were normally distributed; 2) the data obtained from homogeneity testing of significance score from every group >0,05 so that the data were homogeneously distributed; 3) the different testing result obtained from control and treatment group is the significant point of 0.752 >0.05 so there are no significant different.Conclusion: The conclusion that can be taken from the research are: 1) There is a high increase of MDA level in muay thai athlete who is given HITT training method ; 2) Giving the dragon fruit to the muay thai athlete which is given HIIT training method proven successfully decrease the level of their MDA; 3) There was no significant difference in effect between muay thai athletes who consumed dragon fruit and muay thai athletes who only practiced using the HIIT training method towards the decrease of MDA level within the blood.